The influence of human resources Accounting on cost reduction - عبيد انتصار احمد (Journal of Economics and Administrative Sciences, 2018)
The development of human resources training programs has an applied and important role in the preparation of human cadresin terms of capacity to absorb technical sciences and skills and scientific and practical practices at faster rates in order to bealighed with continous development. Hence the recognition of the significant role that human resources play in the economy of any country,which has stressed the interest towards the economic unity of the qualified staff that it needsin atimely manner through the ongoing training process in the era of high technology day by day In this regard ,the current research deal with accounting of human resources and its impact on reducing costs in the military establishment and then the realit of training and development in this institution. finally ,we have come into the conclusions and recommendatios ,the most important conclusions is that if the military cadets are trained by acadre from within the institution ,the training costs do not appear.The Iraqi training staff dues not receive any fees for this training. The members are also sent to courses outside the country in order to develop them and raise their competences where the Foreign wages in hard currency for each member trained. The most important recommendations are that human resources is awealth not only for the economic units but for the state itself and all that has been up graded skills led to contribute to economic progress and also stressed the need to train qualified Iraqi cadres outside the country for the purpose of development and benefit from their experience in training associates within the country,in providing the cost of foreign trainer.